Searching for Understanding in Cross-Cultural Communication - Larina, Tatiana (Respectus Philologicus, 2013)
In our globalized and multicultural world, the problem of understanding is crucial. It is the concern not only of politicians, sociologists, and psychologists, but also a key subject of linguists, translators, language and culture teachers, and specialists of other fields sensitive to cross-cultural issues. This was once again demonstrated at the international conference Cross-cultural Pragmatics at a Crossroads III, held from 26–28 June 2013 at the University of East Anglia, Norwich, UK.